Nutrient Use Efficiency: from Basics to Advances - Rakshit, Amitava (Springer, 2015)
This book addresses in detail multifaceted approaches to boosting nutrient use efficiency (NUE) that are modified by plant interactions with environmental variables and combine physiological, microbial, biotechnological and agronomic aspects. Conveying an in-depth understanding of the topic will spark the development of new cultivars and strains to induce NUE, coupled with best management practices that will immensely benefit agricultural systems, safeguarding their soil, water, and air quality.